Diagnostic differences and agreement between the original and revised European Working Group (EWGSOP) consensus definition for sarcopenia in community-dwelling older adults with type 2 diabetes mellitus. (July 2020) - Villani, Anthony; McClure, Rebecca; Barrett, Michelle; Scott, David
Highlights: Sarcopenia has emerged as a unique complication in patients with T2DM. The operationalization of a consensus definition for sarcopenia is needed to support implementation of timely lifestyle interventions. The EWGSOP definition is one of the more recognizable consensus definitions in the research literature and has recently been updated. It is unknown whether such revisions will impact sarcopenic case findings. We report significant discordance and limited overlap in sarcopenic case findings when applying both EWGSOP operational definitions. This finding is likely due to the conservative modifications to the diagnostic criteria for muscle mass and muscle strength. Abstract: Aim: We aimed to compare diagnostic differences for identification of sarcopenia using the original operational definition developed by the European Working Group on Sarcopenia in Older People (EWGSOP1) and the most recently revised EWGSOP2 definition in community dwelling older adults with type 2 diabetes mellitus (T2DM). Methods: Appendicular Lean Mass (ALM) corrected for height (ALM/m 2 ) was assessed by dual energy X-ray absorptiometry. Muscle strength was assessed using hand-grip strength (HGS) or chair stands, and the Short Physical Performance Battery (SPPB) and gait speed were used to evaluate lower extremity physical function. Cohen's kappa (κ) statistic was applied to determine the degree of agreement between the two definitions. Chi-square analysis with Bonferroni post hoc corrections were applied to determine differences in the prevalence of sarcopenic case-findings. Results: A total of n = 87 older adults (71.2 ± 8.2 years; 66.7% males; BMI: 29.5 ± 5.8 kg/m2) were included. Agreement between the two definitions was low and non-significant (κ value = 0.118; P = 0.144). Significantly more cases of sarcopenia were identified when applying the EWGSOP1 definition (EWGSOP1: n = 6 (7%); EWGSOP2: n = 2 (2%); P = 0.004). No sex specific differences were observed. Only 2 of the 6 (33.3%) cases of sarcopenia identified by EWGSOP1 were also identified as sarcopenic when applying the EWGSOP2 diagnostic criteria. Conclusions: We showed significant discordance and limited overlap in the number of sarcopenic case-findings when applying both EWGSOP definitions. It is unknown as to whether the new diagnostic criteria are better at identifying adverse clinical outcomes in patients with T2DM. Future investigation is therefore warranted.